BASIS PLURALIS-MULTIKULTURAL DI PESANTREN - Ahmad Zaenuri; Irja Putra Pratama (Conciencia, 2019)
This article aims to reveal the role of Nahdlatul Ulama culture boarding schools in instilling plurality and multicultural values in their education system. The focus of his research was conducted on two pesantren. Pesantren Salafiyah Syafiiyah and Pesantren Sirojut Tholibin Gorontalo. The research method used is qualitative with a phenomenological approach. The data collection is done by interviewing the leaders of the pesantren and related parties. The information obtained is then reviewed and adjusted to data from observations and documentation. In this study the authors use educational theories about in, at and beyond the wall. Through the concept of education in the wall, the pesantren emphasizes lessons only on the religion it adheres to tafaqquh fi al-din without conducting dialogue on other religions. Meanwhile, through the concept at the wall, the pesantren does not only try to understand the religion it adopts, but also other religions. Meanwhile, the concept of beyond the wall pesantren requires not only understanding, but also living together in communities of different religions. Based on the results of the study concluded thatthe Pesantren Salafiyah-Syafiiyah and the Pesantren Sirojut Tholibin have been shown to have a significant role in establishing multicultural-pluralist values in accordance with the basic principles of the Nahdlatul Ulama-an. Basic principles such as Ukhuwah Wathaniyah (Brotherhood on the basis of equality of nationality / nationalism), Ukhuwah Insaniyyah (Brotherhood on the basis of humanity), to the attitudes of al-Ikhlas (sincerity), al-Adalah (justice), al-Tawassut (moderation), al-Tawazzun (balance), al-Tasamuh (tolerance) manifested in pesantrenan activities.